MoU signing ceremony between Universiti Teknologi MARA Cawangan Pulau Pinang and Xavier University - Ateneo de Cagayan / Aileen Farida Mohd Adam, Nazima Versay Kudus and Noor Azli Affendy Lee - Mohd Adam, Aileen Farida; Kudus, Nazima Versay; Affendy Lee, Noor Azli (Academy of Language Studies, 2022)
A Memorandum of Understanding (MoU) signing ceremony between Universiti Teknologi MARA Cawangan Pulau Pinang, Malaysia (UiTMCPP) and Xavier University - Ateneo de Cagayan, Philippines (XU) was held from 9 a.m. to 10 a.m., Friday, 9 September 2022 via Google Meet. The ceremony was hosted by UiTMCPP and led by the initiators of the MoU, Mdm. Aileen Farida Mohd Adam, Mdm. Nazima Versay Kudus and Mr. Noor Azli Affendy Lee, who are also English Language lecturers at the Academy of Language Studies, UiTMCPP. The momentous occasion was officiated by the Deputy Rector (Academic and International Affairs), exercising the functions of the Rector of UiTMCPP, Assoc. Prof. Ir. Dr. Ahmad Rashidy Razali and the President of Xavier University - Ateneo de Cagayan, the Honorable Dr. Fr. Mars P. Tan SJ. The signing ceremony was witnessed by the Deputy Rector (Student Affairs) of UiTMCPP, Ts. Dr. Basharudin Abdul Hadi as well as the executive members and representatives from both universities.